Peranan kecerdasan emosional terhadap prestasi belajar siswa - Ibrahim, Ibrahim; Randabunga, Berta; Gultom, Rismawaty (Davar : Jurnal Teologi, 2023)
ABSTRACTThis research was conducted with the aim of analyzing and testing how much influence students' emotional intelligence has on the learning achievement of students in grades 5 and 6. This research uses quantitative methods. Quantitative research methods are methods for testing certain theories by testing validity, reliability and simple regression. This research was carried out at YHS Makassar Christian Elementary School. All 54 students in grades 5 and 6 in the 2021/2022 academic year were included as the sample. Based on the results of the data management carried out, it was found that there was an influence of students' emotional intelligence on student learning achievement at YHS Makassar Christian Elementary School which was supported by the table above regarding variable relationships, which was included in the sufficient category with a value of 0.469. There is an influence of students' Emotional Intelligence on student learning achievement at YHS Makassar Christian Elementary School. In accordance with research results which show that students' emotional intelligence on student learning achievement has an influence of 22%, the remaining 78% is influenced by other factors or variables. Keywords: Emotional Intelligence, Learning achievement, Student ABSTRAKPenelitian ini dilakukan bertujuan untuk menganalisa dan menguji berapa besar pengaruh kecerdasan emosional siswa, terhadap prestasi belajar siswa kelas 5 dan 6. Penelitian ini menggunakan metode kuantitatif. Metode penelitian kuantitiaf merupakan metode-metode untuk menguji teori tertentu dengan cara uji validitas, reliabilitas dan regresi sederhana. Penelitian ini dilaksanakan di SD Kristen YHS Makassar. Seluruh siswa kelas 5 dan 6  di Tahun pelajaran 2021/2022 sejumlah 54 siswa dimasukkan sebagai sampel. berdasarkan hasil pengelolaan data yang dilakukan, didapat bahwa adanya pengaruh kecerdasan emosional siswa terhadap prestasi belajar siswa di SD Kristen YHS Makassar yang didukung oleh tabel di atas tentang hubungan variabel termasuk dalam kategori cukup dengan nilai 0,469. Terdapat pengaruh kecerdasan emosional siswa terhadap prestasi belajar siswa di SD Kristen YHS Makassar. Sesuai dengan hasil penelitian yang memperlihatkan bahwa kecerdasan emosional siswa terhadap prestasi belajar siswa memiliki pengaruh sebesar 22%, sisanya sebesar 78% dipengaruhi oleh faktor atau variable lainnya.Kata Kunci: Kecerdasan Emosional, Prestasi Belajar, Siswa.